2022
DOI: 10.1007/s10856-022-06684-1
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin-modified Hydroxyapatite coating promotes the osseointegration of titanium rods by activation SIRT1/SOD2 signaling pathway in diabetic rats

Abstract: The purpose of this study is to investigate the role of Silibinin (SIL)-modified Hydroxyapatite coating on osseointegration in diabetes in vivo and in vitro and explore the mechanism of osteogenic differentiation of MC3T3-E1. RT-qPCR, Immunofluorescence, and Western blot were used to measure the expression level of oxidative Stress Indicators and osteogenic markers proteins. Moreover, CCK-8 assay was conducted to detect cell viability in hyperglycemia. Alizarin red staining and alkaline phosphatase staining we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…44 SOD2 is one of the most important antioxidant enzymes in the body, and it is primarily responsible for neutralizing superoxide radicals, which are highly reactive and can cause significant damage to cells and tissues. 26,45 Hence, in this investigation, we further explored the influence of VIT on the differentiation of osteoblasts when exposed to increased levels of oxidative stress. As expected, VIT displayed a safeguarding effect on osteoblast differentiation due to its antioxidant characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…44 SOD2 is one of the most important antioxidant enzymes in the body, and it is primarily responsible for neutralizing superoxide radicals, which are highly reactive and can cause significant damage to cells and tissues. 26,45 Hence, in this investigation, we further explored the influence of VIT on the differentiation of osteoblasts when exposed to increased levels of oxidative stress. As expected, VIT displayed a safeguarding effect on osteoblast differentiation due to its antioxidant characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the beneficial effect of the systemic administration of silibinin, local delivery of drugs is preferable to systemic application for periodontal treatment due to its relative safety and immediate effects at the action site (Wei et al, 2021). Silibinin has been locally made into coating that greatly enhanced bone regeneration (Tao et al, 2022). Furthermore, silibinin has been developed as injectable, biodegradable hydrogels (Cho et al, 2012), which might be an efficient delivery system for silibinin in treating DP.…”
Section: Discussionmentioning
confidence: 99%
“…After a week, rats with random blood glucose concentration higher than 250 mg/dL (13.89 mmol/L) could be defined as T1DM. Referring to the methods of Tao et al, we maintained the diet for 90 days to study the effects of diabetes on bone [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Seminal discoveries have deconstructed the bone microenvironment into a unique niche composed of multiple cellular and extracellular components and shown the devastating influence of the diabetic microenvironment on bone metabolism [ 16 ]. Osteoblasts play a central role in bone formation, while ROS also reduce osteoblast activity and functional response [ 17 ]. Ma et al found that ROS accumulation in type 2 diabetes led to mitochondrial dysfunction and ferroptosis in osteoblasts [ 18 ].…”
Section: Introductionmentioning
confidence: 99%